2018
DOI: 10.1186/s12934-018-0973-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and high-efficiency secreted expression in Bacillus subtilis of a thermo-alkaline β-mannanase from an alkaliphilic Bacillus clausii strain S10

Abstract: Backgroundβ-Mannanase catalyzes the cleavage of β-1,4-linked internal linkages of mannan backbone randomly to produce new chain ends. Alkaline and thermostable β-mannanases provide obvious advantages for many applications in biobleaching of pulp and paper, detergent industry, oil grilling operation and enzymatic production of mannooligosaccharides. However, only a few of them are commercially exploited as wild or recombinant enzymes, and none heterologous and secretory expression of alkaline β-mannanase in Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Kinetic analysis showed that when using locust bean gum as a substrate, the V max and K m of 30a/BSM were 1238 ± 55.54 μmol/min/mg and 3.74 ± 0.40 mg/mL (Table ), respectively, indicating that BSM was a typical endomannanase with moderate catalytic ability . Though thermostability was impressively improved, the K m was not altered by molecular cyclization .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kinetic analysis showed that when using locust bean gum as a substrate, the V max and K m of 30a/BSM were 1238 ± 55.54 μmol/min/mg and 3.74 ± 0.40 mg/mL (Table ), respectively, indicating that BSM was a typical endomannanase with moderate catalytic ability . Though thermostability was impressively improved, the K m was not altered by molecular cyclization .…”
Section: Resultsmentioning
confidence: 99%
“…To assess the thermostability, all linear, cyclized, and relinearized enzymes were preincubated in citrate/phosphate buffer (pH 6.0) at 50−70 °C for 1 h. Aliquots were taken at different time intervals (2,5,10,20,30, and 60 min) and subjected to activity assays under the optimal conditions (pH 6.0, 50 °C). The initial activities before preincubation were taken as 100%.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… and Zhou et al. have characterized Bacillus‐ derived β‐mannanases with optimal activity at pH 6 and 9.5, respectively.…”
Section: Resultsmentioning
confidence: 99%